2008
DOI: 10.1042/bj20071423
|View full text |Cite
|
Sign up to set email alerts
|

ODCp, a brain- and testis-specific ornithine decarboxylase paralogue, functions as an antizyme inhibitor, although less efficiently than AzI1

Abstract: ODC (ornithine decarboxylase), the first enzyme in the polyamine biosynthesis pathway in mammalian cells, is a labile protein. ODC degradation is stimulated by Az (antizyme), a polyamine-induced protein, which in turn is regulated by an ODC-related protein termed AzI (Az inhibitor). Recently, another ODCp (ODC paralogue) was suggested to function as AzI, on the basis of its ability to increase ODC activity and inhibit Az-stimulated ODC degradation in vitro. We show in the present study that ODCp is indeed capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…We identiWed and cloned the cDNA of a novel human ODC-like protein called ODC paralogue (ODC-p) (Pitkanen et al 2001), and recently, we demonstrated that ODC-p is indeed a novel form of AZIN (Kanerva et al 2008). Our Wndings were conWrmed by Snapir et al (2008). Moreover, Lopez-Contreras et al (2006) reported that also the murine paralogue of ODC-p acts as an AZIN.…”
Section: Introductionmentioning
confidence: 48%
“…We identiWed and cloned the cDNA of a novel human ODC-like protein called ODC paralogue (ODC-p) (Pitkanen et al 2001), and recently, we demonstrated that ODC-p is indeed a novel form of AZIN (Kanerva et al 2008). Our Wndings were conWrmed by Snapir et al (2008). Moreover, Lopez-Contreras et al (2006) reported that also the murine paralogue of ODC-p acts as an AZIN.…”
Section: Introductionmentioning
confidence: 48%
“…Our results on COS7 cells also support that AZIN1 increases polyamine uptake, at least as efficiently as AZIN2. Recently, Snapir et al (42) found that AZIN2, stably transfected into NIH 3T3 cells, exerted a modest increase on the spermidine uptake rate (less than 20%), when compared with the effect of AZIN1 (about 100%), concluding that AZIN2 is less potent than AZIN1 in regulating polyamine uptake. The higher increase in polyamine uptake rate produced by both AZINs (about 300%) in our system in comparison with that observed in stably transfected cells could be related with a lower AZs/AZINs ratio.…”
Section: Discussionmentioning
confidence: 99%
“…ODCp was demonstrated to lack ornithine decarboxylase and arginine decarboxylase activity, but is able to rescue ODC from degradation and to inhibit the antizyme-mediated inhibition of polyamine uptake; therefore, it was termed antizyme inhibitor 2 [109][110][111][112][113]. Like antizyme inhibitor 1, antizyme inhibitor 2 is also rapidly degraded in a ubiquitin-dependent manner [111,113]; it stimulates ODC activity, polyamine uptake and cellular proliferation although less efficiently than antizyme inhibitor 1 [113]. Antizyme inhibitor 2 and antizyme 3 are both expressed in the haploid germinal cells, a location different from that of ODC mRNA, which localizes predominantly to the outer part of the seminiferous tubules.…”
Section: Antizyme Inhibitormentioning
confidence: 99%